CloudAM 2018 workshop chairs welcome message - Bittencourt, Luiz Fernando, 1981- (2019)
Abstract: Presents the introductory welcome message from the conference proceedings. May include the conference officers' congratulations to all involved with the conference event and publication of the proceedings record. CloudAM 2018 Workshop Chairs Welcome Message - Welcome to the seventh edition of the International Workshop on Clouds and (eScience). Applications Management (CloudAM 2018). Cloud computing, virtualization and virtual (eScience) applications are currently subjects with a substantial and undergoing study. As a result, they have been generating substantial interest in the community, and it is anticipated that this interest will continue to expand. It is also important to the research community as it is challenging traditional methods by its sheer size and high level of automation. Clouds must provide appropriate levels of performance to large groups of diverse users, and those clouds are accessed through virtualized wide area networks. Management systems are essential for that and thereby for the future success of the cloud paradigm. New systems, methods, and approaches for cloud, virtualization and (eScience) applications management are to be discussed at this workshop. In order to provide appropriate levels of performance to large groups of diverse users, and in order for clouds to be accessed through virtualized wide area networks, it is important for the research community to continue to address these topics as traditional methods are being challenged by their sheer size and level of automation. Management systems are essential for that and thereby for the future success of the cloud paradigm. The CloudAM 2018 aims at placing a forum of discussion about new ideas, application experiences, open problems, as well as problems being addressed by the cloud computing community. This year, we received submissions, addressing topics such as economic clouds, workflow systems, scheduling and resource allocation, real scientific experience with private clouds, specific hardware for parallel computing, and cloud federations. The variety of topics allowed us to compose an interesting program with 9 selected papers. We would like to thank all the authors for their contribution, all the reviewers for their constructive comments and feedback to the authors, as well as the technical program committee for helping to shape this seventh CloudAM edition. Finally, the CloudAM organizers would like to thank the organizers of the UCC for the opportunity and for their cordiality in hosting this workshop. Luiz F. Bittencourt, University of Campinas (UNICAMP), Brazil - Bruno Schulze, National Lab for Scientific Computing (LNCC), Brazil - Rafael Tolosana-Calasanz, Universidad de Zaragoza, Spain CloudAM 2018 Workshop Chairs